Prototyping the institutions of the future: the case of the Civic Innovation Laboratories (LABIC) - Pascale, Pablo; Resina, Jorge (Iberoamerican Journal of Development Studies, 2020)
The crisis of institutional trust has led governments and international organizations to seek new channels for connecting with citizens. Citizen labs are, possibly, the most innovative response that has emerged to create civic engagement and build an alternative development agenda, promoting new participatory processes oriented towards Sustainable Development Goals (SDGs). This paper is focused on a case study, the Civic Innovation Laboratories (LABIC) of the Ibero-American General Secretariat, to identify some keys for institutional renewal. Four are the main lessons we learn: a) experimental solutions through prototyping and trial-error; b) transformation (systemic and simultaneous) in three levels (citizen, institutional and cooperation); c) social thermometer with double functionality, problems and solutions proposed by communities and citizens, and d) institution worked as an organic system, in continuous evolution.